Analgesic activity of allopurinol and febuxostat in experimental animals - P. Sahu, Yajnesh; Pandey, Sachchidanand; Mohapatra, Sabita (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Currently, two classes of analgesics, nonsteroidal anti-inflammatory drugs (NSAIDs) and opioid analgesics are used to manage pain in different clinical situations. Chronic uses of these drugs have various adverse effects like gastric ulceration/bleeding, analgesic nephropathy and respiratory depression, physical dependence, addiction, respectively. Xanthine oxidase inhibitors, used for chronic gout, might have a role in alleviation of pain, as per literature survey. Hence, the present study was carried out to evaluate the potential analgesic activity of allopurinol and febuxostat in different experimental models. Methods: The analgesic activity of allopurinol and febuxostat was assessed by employing two different experimental pain models-tail flick latency model in rats for central analgesia and acetic acid induced writhing model in mice for peripheral analgesia and was compared with tramadol and aspirin. Results: Allopurinol and febuxostat produced significant central and peripheral analgesic effects as is evident from increase in reaction time in tail flick test and inhibition in number of writhes in acetic acid induced writhing test. Conclusions: The results of the present study demonstrate marked analgesic effect of allopurinol and febuxostat.